EVALUASI KELAYAKAN FINANSIAL DAN KEUNTUNGAN PETERNAKAN AYAM RAS PETELUR PT SPU DAN AF DI KECAMATAN JATI AGUNG KABUPATEN LAMPUNG SELATAN - Wicaksono, Danang; Zakaria, Wan Abbas; Widjaya, Sudarma (Jurnal Ilmu-Ilmu Agribisnis, 2020)
This research aims to know the financial feasibility evaluation and profitability at PT. SPU and AF in Jati Agung Sub-district of South Lampung Regency. This research location was selected purposively. The data was collected in October - December 2018. The research method used was comparative study. This research compares between PT SPU with AF. The respondents include the owners of each layer farm. The data analysis method used was qualitative and quantitative descriptive analysis. The data analysis using profit analysis, Internal Rate of Return (IRR), Net Present Value (NPV), Payback Period (PP), Gross Benefit Cost Ratio (Gross B/C), Net Benefit Cost Ratio (Net B/C).with interest rate of 9 percent. The result showed that PT SPU and AF was profitable and can con continue to be developed. Financially, the business is still viable because the NPV and Net B/C is higher than 1, and the value of IRR is higher than the interest rate. Keywords: agribusiness system, layer, profit